PROFIL TINGKAT KECEMASAN AKADEMIK MAHASISWA AKHIR DITINJAU DARI JENIS KELAMIN - Jamain, Ririanti Rachmayanie; Zahidah, Asih Nor; Syammari, Shoofii (Universitas Tanjungpura, 2026)
Final-year students frequently encounter academic anxiety as a result of the pressures associated with completing their thesis. This research aimed to examine the level of academic anxiety among final-year students with a focus on gender differences. A quantitative research method was utilized through a survey approach, involving 196 final-year students from Lambung Mangkurat University. Data collection was conducted using an academic anxiety scale adapted from Ottens. The data were analyzed through descriptive statistical methods and the Mann-Whitney U Test. The findings revealed no statistically significant difference in overall academic anxiety levels between male and female students. Nevertheless, female students were observed to experience higher levels of physiological distress in comparison to their male peers.